Why The Concept Of "Quantum Brain" Was Not Discovered In 1940s - BAŞAR, EROL (Anka Publisher, 116-11 Sok No.10 K 2 D 2, Bornova, Izmir 35050, Turkey, 2010)
Already in 1940s several neurophysiologic, biochemical and physical discoveries took place and the conjecture was open for the initiation of the "Quantum Brain Concept". The present essay explains the ensemble of discoveries that could lead to the quantum brain concept and tries to find out the reason, why this concept was delayed during many decades.
Keywords: EEG; quantum brain; visual-cortex; synchronization; oscillations; integration; cat; kuantum beyin; görsel korteks; senkronizasyon; salınımlar; bütünleşme; kedi